Soil CO2 efflux from a podzolic forest soil before and after forest clear-cutting and site preparation - Pumpanen, J.; Westman, C. J.; Ilvesniemi, H. (Boreal Environment Research Publishing Board, 2024)
The effect of forest harvesting and subsequent site preparation on soil CO2 efflux was studied on a clear-cut site with five soil treatments, including mounding, exposed E- and C-horizons, and undisturbed soil with and without logging residue left on soil. Site preparation accounted for over 75% of the total variance in soil CO2 effluxes. Clear-cutting and removal of logging residue decreased instantaneous CO2 effluxes from the soil surface by 40%, whereas the highest instantaneous effluxes were measured from mounds and from undisturbed soil with logging residue. These sampling points showed effluxes twice as high as those in the control forest or in places where the logging residue was removed. The lowest instantaneous effluxes, about 18% of those in the control forest, were measured from the exposed C-horizon. Annual effluxes in the forest were 1900 g CO2 m–2 before harvesting and 3242, 2845, and 2926 g m–2 in the three successive years after harvesting in places with logging residue, but when logging residue was removed, the annual efflux decreased to pre clear-cutting levels. Annual CO2 efflux from the logging residue was 1423 g m–2 during the first year after clear-cutting equaling 388 g m–2 of C assuming even distribution of logging residue on the site. Thus, some 23% of the total C pool in the above-ground logging residue was released during the first year after clear-cutting. The estimated annual C emissions from the O-, E- and B-horizons were 352 g m–2 during the first year after clear-cutting. Assuming that this compounded emission originated from the decomposition of roots, this would make about 20% of measured root biomass on the site. The decomposition rate was also fastest during this period, slowing in subsequent years. Based on the measured CO2 evolution rate, the reduction observed in the decomposition rate, and the aging of decomposing material, we believe that the decomposition of logging residue is a slow process. Consequently substantial amounts of non-decomposed material still may remain at ...